1976
DOI: 10.1002/bjs.1800630309
|View full text |Cite
|
Sign up to set email alerts
|

Parietal pleurectomy for recurrent pneumothorax

Abstract: One hundred patients with persistent or recurrent pneumothorax treated by parietal pleurectomy are described. There was one known recurrence and no postoperative deaths. Six patients required further surgery for complications. In the uncomplicated cases the average stay in hospital following operation was 11-5 days. Parietal pleurectomy should be regarded as the treatment of choice for patients with recurrent pneumothorax who are fit to undergo surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
3

Year Published

1981
1981
2002
2002

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 11 publications
1
4
0
3
Order By: Relevance
“…This procedure may be associated with a considerable amount of pain and an unacceptably high recurrence rate (9, and Gaensler (6) reported much better results, with the operation of parietal pleurectomy. There have been two recent reports in which parietal pleurectomy was considered an important feature of the surgical management of spontaneous pneumothorax (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure may be associated with a considerable amount of pain and an unacceptably high recurrence rate (9, and Gaensler (6) reported much better results, with the operation of parietal pleurectomy. There have been two recent reports in which parietal pleurectomy was considered an important feature of the surgical management of spontaneous pneumothorax (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Pleurectomy was used to treat recurrent spontaneous pneumothorax for the first time in 1956, in nine patients [74]. In the following years, partial pleurectomy or pleural abrasion became standard therapy, especially for recurrent spontaneous pneumothorax, and resulted in average recurrence rates of 1% [9,[75][76][77]. Combined pleurectomy and bullectomy showed average recurrence rates of 2% [7,13,14,17,78,79].…”
Section: Surgical Therapymentioning
confidence: 99%
“…Reviewing the results of VATS in 805 patients with spontaneous pneumothorax, the mean recurrence rate was 4% (table 4) [10][11][12][80][81][82][83][84][85][86][87][88][89][90][91], which was higher than the mean recurrence rate of 1.5% after conventional surgical therapy (table 3) [7,9,13,14,17,[74][75][76][77][78]. However, several studies that have reported comparative analysis of VATS versus conventional thoracotomy have shown reduced operation time, drainage time and complication rates after VATS, resulting in shorter hospital stay and a more rapid return to the normal daily activities of the patients [84,92,93].…”
Section: Surgical Therapymentioning
confidence: 99%
“…Die alleinige intrathorakale Drainage hat mit 20-30% im Mittel zwar die höchste Rezidivrate, ist aber zumindest in chirurgischen Einrichtungen, die nicht mit der Videothorakoskopie vertraut sind, Standard beim Erstereignis [2,22]. Die alleinige intrathorakale Drainage hat mit 20-30% im Mittel zwar die höchste Rezidivrate, ist aber zumindest in chirurgischen Einrichtungen, die nicht mit der Videothorakoskopie vertraut sind, Standard beim Erstereignis [2,22].…”
Section: Diskussionunclassified
“…Die jährliche Inzidenz wird mit 7-28 Neuerkrankungen pro 100.000 und Jahr angegeben [1,8], das Geschlechtsverhältnis zwischen Männern und Frauen beträgt 4-5:1 [2,10]. 70-80% der Patienten klinisch ohne Rezidiv [1,2,22]. 70-80% der Patienten klinisch ohne Rezidiv [1,2,22].…”
unclassified